Geo-economics of the Global Maritime Fulcrum (GMF) vision of Indonesia - Abeysinghe, Chaminda; Wijesinghe, Hashan (Technium Social Sciences Journal, 2021)
Considering the present context of international relations, trade, investments, tourism and other economic and financial instruments have come to the forefront in determining the nature and scope of interstate relations. Since the end of the Cold War, the world began to give greater emphasis to international economic activities and that in return has made the world highly interdependent, especially in the fields of international trade, investments and financial assistance. These developments in the international arena have made “geo-economics” an area of greater concern. Geoeconomics can be simply defined as the relationship between economic and geographical conditions. Indonesia in 2014, under the leadership of Joko Widodo, initiated Global Maritime Fulcrum (GMF) Vision with the prime objective of becoming a maritime power. Against this backdrop, the main objective of this research is to examine the geoeconomic significance of this GMF vision. As Indonesia is the largest economy in Southeast Asia and an integral part in maritime trade routes, Indonesia’s GMF vision remains highly significant in promoting the economic interests of the country. The research examines how Indonesia can attain its economic interests through the GMF vision. This is desk study and both primary and secondary data is used for the purpose of the study. As per the findings of the study, Indonesia’s maritime economy continues to play a significant role in the country becoming a major economic powerhouse and the level of success which can be achieved by Indonesia as a maritime country would depend on how well it implements the GMF vision. The Belt and Road Initiative of China would complement the GMF vision, while Indonesia should also be vigilant to the major challenges which hinder the country’s ability of realizing the geoeconomic interests. Keywords: Global Maritime Fulcrum, Geoeconomics, Indonesia, Maritime culture,